The role of TASK-like K+ channels in oxygen sensing in the carotid body. - Buckler, K; Williams, B; Orozco, R; Wyatt, C (2006)
The carotid body plays an important role in initiating protective responses to hypoxemia. The primary oxygen sensing cells are the glomus or type 1 cells. Hypoxia evokes the secretion of neurotransmitters from these cells which then excite afferent nerves. This response is mediated via membrane depolarization and voltage-gated Ca2+ entry. Studies from this laboratory have revealed that membrane depolarization in response to hypoxia is primarily the result of inhibition of background K+ channels which show strong similarities to the acid sensitive tandem-P-domain K+ channels TASK-1 and TASK-3. The background K+ channels of type-1 cells are also very sensitive to inhibition of mitochondrial energy metabolism and, in excised patches, appear to be directly activated by ATP. Thus these TASK-like background channels would appear to confer the ability to sense changes in oxygen levels, pH and metabolism upon the type 1 cell. The key issue of whether the effects of hypoxia are mediated through changes in metabolism remains unanswered but the effects of inhibition of mitochondrial energy metabolism and of hypoxia upon background K+ channels is mutually exclusive suggesting that there is a close link between metabolism and oxygen sensing in the type 1 cell.